Impact of design, size, and a combined routine on the plaque removal efficacy of manual, hybrid (powered-mode) and interdental toothbrushes: a robot-assisted in vitro study - Daniel Bacqueville; Mélanie Souyris; Tomas Lang; Alberto Ogalla; Aurélien Simonini; Peter Gängler; Nathalie Castex-Rizzi (BMC Oral Health, 2026)
Abstract Background Regular and effective toothbrushing with interdental cleaning is key to maintaining oral health. Using an in vitro testing system, we compared the plaque removal efficacy of manual toothbrushes with different bristle designs, different-sized interdental brushes (IDBs), and a hybrid brush used in powered mode alone or in a combined routine with IDBs. Methods Manual ( n = 4) and powered (hybrid model; sonic mode) toothbrushing was simulated using a clinically tested robot programme (rotating movement, 2 min, 3.5 N force). IDBs ( n = 8) were evaluated using a standardized hygienist protocol. Tests were carried out on a typodont tooth model and cleaning efficacy was evaluated using computer-assisted optical automatic plaque planimetry. Data were analysed using descriptive statistics, the Kolmogorov-Smirnov test, two-sample t test and Mann-Whitney U test. Results Manual toothbrushes with longer, soft and conical-shaped bristles showed the highest levels of overall in vitro simulated plaque removal: up to 72.6% with improved cleaning efficacy for interdental, gum-line, and root fields under test conditions. IDBs ≥ 1.3 mm were the most effective for removing simulated dental plaque at the poorly accessible mesial and distal sites of the typodont model (up to 77.1%). The combined hybrid powered-mode toothbrushing and hygienist IDB protocol resulted in a significant 15.1% increase in simulated plaque removal (81.5% overall), with the greatest improvement in interdental surface and root fields (values up to 88%). Conclusions These in vitro data provided insights into design characteristics that could potentially improve the cleaning efficacy of manual brushes and highlighted the importance of using appropriately sized IDBs. They also showed that the robot testing system could be used to test hybrid brushes in powered mode, as well as alongside standardized hygienist IDB protocol to evaluate the potential efficacy of combined cleaning routines, which may be useful for providing guidance during the early phases of development of new devices and product ranges.